Christian Theology and the Capabilities Approach: Constructing a Method for Engagement - Heuvel, Steven C. van den (International journal of public theology, 2021)
Abstract This article focuses attention on the capabilities approach, an increasingly influential approach to human development. The case is made that, in light of its popularity, a Christian public theological engagement with this approach is needed. The various attempts that have been made up until now to engage the capabilities approach from the perspective of Christian theology have been lacking in methodological awareness and clarity. On account of this weakness an explicit methodological framework is developed through a revised form of the method of correlation. For that purpose, the work of Paul Tillich, David Tracy and Dan Browning is put to use. What this revised method leads to in practice is examined through a dialogue with Martha Nussbaum (one of the main proponents of the capabilities approach) and Dietrich Bonhoeffer.